Land-Use Law in the United States and Japan: A Fundamental Overview and Comparative Analysis - Byron Shibata (Washington University Journal of Law & Policy, 2002)
Obviously no one article can thoroughly cover all aspects of land-use regulation in Japan, and certainly this Essay does not attempt to do so. However, this Essay does attempt to fully explain the zoning system, as well as other key fundamentals: the major land-use statutes; development bulk and density standards; and rules on nonconformities. In addition to familiarizing the reader about Japanese land-use, this Essay compares the Japanese approach with the approach of some sample U.S. jurisdictions: Portland, Oregon; Chicago, Illinois; and Houston, Texas. A comparative analysis is useful as a reference point not only for understanding differences in legal approaches, but also for ascertaining merits and problems that are difficult to identify through a singular approach. Finally, this Essay is structured to allow the reader to easily access and refer to the presented information, according to the reader’s needs or prior knowledge of the material. Hopefully, the analyses and conclusions in this Essay can also form the basis for further research on land-use issues in Japan and the United States.
Keywords: Land use -- United States; Land use -- Japan; Comparative law; Japan; Land use; United States; Property